2012
DOI: 10.1021/jp302992k
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/Graphene Quantum Dot Solid-State Solar Cell

Abstract: Graphene quantum dots (GQDs) synthesized by a direct chemical method have been used in combination with ZnO nanowires (NWs) to demonstrate their potential as a solar harvesting material in photovoltaic cells exhibiting an open circuit voltage of 0.8 V. The excited state interaction between the photoexcited GQDs and the ZnO NWs has been verified from the charge-transfer process by both emission spectroscopy and photovoltaic measurements. This work has implications for less expensive and efficient next generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(122 citation statements)
references
References 67 publications
(57 reference statements)
1
120
0
1
Order By: Relevance
“…[18] In addition, the related graphene quantum dots have been used as sensitizers in ZnO nanorod-based solar cells, but this carbon material was produced using top-down methods. [19] Such nanostructured solar cells have the potential to be produced at significantly lower costs than traditional silicon and thin-film photovoltaics because the use of a high surface area scaffold, most commonly TiO 2 or ZnO, reduces the required absorber thickness. [20] The most common such device is the dye-sensitized solar cell, which uses TiO 2 sensitized with a ruthenium-based dye.…”
mentioning
confidence: 99%
“…[18] In addition, the related graphene quantum dots have been used as sensitizers in ZnO nanorod-based solar cells, but this carbon material was produced using top-down methods. [19] Such nanostructured solar cells have the potential to be produced at significantly lower costs than traditional silicon and thin-film photovoltaics because the use of a high surface area scaffold, most commonly TiO 2 or ZnO, reduces the required absorber thickness. [20] The most common such device is the dye-sensitized solar cell, which uses TiO 2 sensitized with a ruthenium-based dye.…”
mentioning
confidence: 99%
“…[16][17][18] Indeed, several studies have shown that the principle of using such materials as sensitizers in mesoscopic solar cells is sound, although the reported power conversion efficiencies cannot yet compete with inorganic QD solar cells. [19][20][21][22][23][24] We here classify GQDs as structurally well-defined, carbonrich organic molecules that generally require multi-step synthetic procedures in contrast to CNDs, which are usually synthesized in a single step but do not exhibit a well-defined molecular structure. This differentiation is, however, not universally accepted in the literature, where the terms graphene quantum dot, carbon nanodot and carbon dot are often used interchangeably.…”
Section: Conceptual Insightsmentioning
confidence: 99%
“…10.6b) is extended from 400 to 700 nm while that for MB-GQDs (475-700 nm) is narrow and extended from 475 to 700 nm (centered at 525 nm), giving green luminescence [21]. The PL emission spectra Dutta et al [25] synthesized GQDs by a direct chemical method and in combination with ZnO nanowires. Figure 10.8a shows the microstructure and size distribution of the synthesized GQDs as observed by the TEM.…”
Section: Solar Cell Devicesmentioning
confidence: 99%
“…The maximum of the emission band shifts toward the higher wavelength side as the excitation wavelength is increased from 280 to 420 nm while the intensity decreases rapidly. According to Dutta et al [25], the evolution of the luminescence behavior with a change in the excitation energy is due to the fact that the band gap in these QDs depends on the size and shapes of the sp 2 domains that result from the size distribution of the GQDs. When these GQDs are combined with ZnO NWs, the emission from these QDs is quenched fully in the visible region (Fig.…”
Section: Solar Cell Devicesmentioning
confidence: 99%
See 1 more Smart Citation